Public Higher Education Response to COVID-19 : The Case of Federal Institutions in Southern Brazil (Comparative & International Education Series, 2021)
The COVID-19 pandemic has affected higher education around the world in unprecedented ways. Given the historical centrality of federal higher education institutions (HEIs) for Brazil’s development, the purpose of this chapter is to discuss the initial response of Southern Brazilian public federal HEIs to COVID-19 regarding their social role. We characterize the actions performed in these institutions to mitigate the effects of the pandemic as described in their institutional websites. Results highlight the importance of extension activities and the need for federal public HEIs’ autonomy, assuring them the possibility to construct human development capabilities for the public good.How to cite: Tozini, K., de Souza, C. S. S., Leal, F., & Miorando, B. S. (2022). Public higher education response to COVID-19: The case of federal institutions in Southern Brazil. In J. S. McKeown, K. Bista, & R. Y. Chan (Eds.), Global higher education during COVID-19: Policy, society, and technology (pp. 25-38). STAR Scholars. https://starscholars.org/product/global-education/